2002
DOI: 10.1074/jbc.m203461200
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of the Transferrin Receptor Is Mediated Constitutively by an Integral Membrane Metalloprotease Sensitive to Tumor Necrosis Factor α Protease Inhibitor-2

Abstract: The transferrin receptor (TfR) is a transmembrane protein that mediates cellular uptake of iron. Although the serum concentration of the soluble TfR (sTfR) is altered in several diseases and used for diagnostic purposes, the identity and regulation of the shedding protease is unknown. In this study we quantified sTfR release from microsomal membranes and leukocytic cell lines in the presence of numerous protease inhibitors and cell activating compounds. We show that sTfR release is mediated by an integral memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 70 publications
4
43
0
Order By: Relevance
“…This supports previous experiments where we induced CD21 shedding by BCR/CD40 crosslinking and by PMA/CaI stimulation (Masilamani et al, 2003a). Recent reports have shown that shedding of several other proteins such as pro-EGF (Le Gall et al, 2003), the transferrin receptor (Kaup et al, 2002) or betaglycan (Velasco-Loyden et al, 2004) are also activated by pervanadate.…”
Section: Discussionsupporting
confidence: 76%
“…This supports previous experiments where we induced CD21 shedding by BCR/CD40 crosslinking and by PMA/CaI stimulation (Masilamani et al, 2003a). Recent reports have shown that shedding of several other proteins such as pro-EGF (Le Gall et al, 2003), the transferrin receptor (Kaup et al, 2002) or betaglycan (Velasco-Loyden et al, 2004) are also activated by pervanadate.…”
Section: Discussionsupporting
confidence: 76%
“…TAPI-2 has been employed as a potent inhibitor of TACE proteolysis in vivo and in vitro (Kaup et al, 2002;Lomniczi et al, 2006). However, ADAM10 is capable of analogous a-cleavage of APP and TNFa, and like TACE, activates many EGFR proligands as well (Blobel, 2005;Kaup et al, 2002;Sahin et al, 2004). Here, we found ADAM10 transcription was increased several-fold in the SVZ following stroke.…”
Section: Discussionmentioning
confidence: 62%
“…24 Alternatively, the lower molecular weight form could be the result of proteolytic events that only occur in some cell types, such as erythroblasts in the case of TfR1. 25,26 The association between EpoR and TfR2 was found to be constitutive, although association of TfR2 with the cell surface form of EpoR was always slightly elevated in Epo-stimulated cells (Figure 2A), suggesting that Epo binding could strengthen the association between both proteins. EpoR western blots further revealed 2 bands that have been already thoroughly characterized and that differ in size due to glycosylation.…”
Section: Association Between Tfr2 and Epormentioning
confidence: 99%